Kinetic and structural analysis of fluorescent peptides on cotton cellulose nanocrystals as elastase sensors. (13th February 2015) - Edwards, J. Vincent; Prevost, Nicolette T.; French, Alfred D.; Concha, Monica; Condon, Brian D.
Highlights: Cotton cellulose nanocrystals were conjugated to small fluorescent peptide. From a cellulose I X-ray diffraction pattern a crystallite size of 58.5 Å was calculated. A tripeptide conjugate has enhanced efficiency in human neutrophil elastase recognition. The peptide–cellulose nanocrystals demonstrate sensitive fluorescent elastase detection. A peptide–cellulose nanocrystal model consistent with degree of substitution levels was built. Abstract: Human neutrophil elastase (HNE) and porcine pancreatic elastase (PPE) are serine proteases with destructive proteolytic activity. Because of this activity, there is considerable interest in elastase sensors. Herein we report the synthesis, characterization, and kinetic profiles of tri- and tetrapeptide substrates of elastase as glycine-esterified fluorescent analogs of cotton cellulose nanocrystals (CCN). The degree of substitution of peptide incorporated in CCN was 3–4 peptides per 100 anhydroglucose units. Glycine and peptide–cellulose–nanocrystals revealed crystallinity indices of 79 and 76%, respectively, and a crystallite size of 58.5 Å. A crystallite model of the peptide–cellulose conjugate is shown. The tripeptide conjugate of CCN demonstrated five-fold greater efficiency in HNE than the tripeptide in solution judged by its k cat / K m of 33, 515. The sensor limits of detection at 2 mg of the tri- and tetrapeptide CCN conjugates over a 10 min reaction time course were 0.03 U/mL PPE and 0.05 U/mL HNE, respectively.